Elemental Profiling of Rice FOX Lines Leads to Characterization of a New Zn Plasma Membrane Transporter, OsZIP7 - Ricachenevsky, Felipe K.; Punshon, Tracy; Lee, Sichul; Oliveira, Ben Hur N.; Trenz, Thomaz S.; Maraschin, Felipe dos Santos; Hindt, Maria N.; Danku, John; Salt, David E.; Fett, Janette P.; Guerinot, Mary Lou (Frontiers in Plant Science, 2018)
Iron (Fe) and zinc (Zn) are essential micronutrients required for proper development in both humans and plants. Rice (Oryza sativa L.) grains are the staple food for nearly half of the world’s population, but a poor source of metals such as Fe and Zn. Populations that rely on milled cereals are especially prone to Fe and Zn deficiencies, the most prevalent nutritional deficiencies in humans. Biofortification is a cost-effective solution for improvement of the nutritional quality of crops. However, a better understanding of the mechanisms underlying grain accumulation of mineral nutreints is required before this approach can achieve its full potential. Characterization of gene function is more time-consuming in crops than in model species such as Arabidopsis thaliana. Aiming to more quickly characterize rice genes related to metal homeostasis, we applied the concept of high throughput elemental profiling (ionomics) to Arabidopsis lines heterologously expressing rice cDNAs driven by the 35S promoter, named FOX (Full Length Over-eXpressor) lines. We screened lines expressing candidate genes that could be used in the development of biofortified grain. Among the most promising candidates, we identified two lines ovexpressing the metal cation transporter OsZIP7. OsZIP7 expression in Arabidopsis resulted in a 25% increase in shoot Zn concentrations compared to non-transformed plants. We further characterized OsZIP7 and showed that it is localized to the plasma membrane and is able to complement Zn transport defective (but not Fe defective) yeast mutants. Interestingly, we showed that OsZIP7 does not transport Cd, which is commonly transported by ZIP proteins. Importantly, OsZIP7-expressing lines have increased Zn concentrations in their seeds. Our results indicate that OsZIP7 is a good candidate for developing Zn biofortified rice. Moreover, we showed the use of heterologous expression of genes from crops in A. thaliana as a fast method for characterization of crop genes related to the ionome and potentially useful in biofortification strategies.